PERAN KYAI UNTUK MENINGKATKAN SPIRITUAL QUOTIENT - Baihaqi, Ahmad (Dakwah, 2017)
According to Durkheim, the most basic socio-religious character of every belief lies in "the Sacred". In any religious community, the world is divided into two separate parts, the "sacred world" and the "profane world";these twoare not similar to natural and supernatural. Sacred elements are always interpreted as something superior, powerful, and, under normal conditions, untouched and always respected. Conversely, profane elements are parts of daily life and ordinary. The main concentration of religion lies in the Sacred .